(untitled) (Research in Agriculture Livestock and Fisheries, 2021)
An experiment was conducted at Sher-e-bangla Agricultural University during May to July, 2016 to examine the morpho-physical potentiality of eight green manure species and these species are viz. Sesbania aculeata, Sesbania rostrata, Crotalaria juncea, Vigna unguiculata, Vigna mungo, Vigna radiata, Leucaena leucocephala and Mimosa pudica. Leaves number, biomass production and nodulation are an important character of any green manuring crops as these crops are very potential for increasing soil fertility after incorporation. The growth habits of these species were studied from 15 DAS to 45DAS whereas dry matter/plant and nodulation data were taken from 25 DAS to 50DAS. At 45DAS, Sesbania aculeata, Sesbania rostrata and Vigna unguiculata shown 53% to 149% higher plant height compared to Vigna mungo, although C. juncea performed better at 30DAS compared to V. unguiculata. Again, C. juncea along with S. rostrata and S. aculeata gave the highest fresh biomass (24% to 72%), dry biomass (2.6t/ha to 5.25t/ha), dry matter plant-1 (60% to 83%) and nodulation compared to rest green manures at 45DAS whereas V. unguiculata produced higher dry matter plant-1 at 20DAS but later it declined insignificantly at 50DAS.The lowest performance was observed from V. mungo followed by V. radiata and M. pudica. It was shown that S. rostrata, S. aculeata, C. juncea, V. unguiculata and L.leucocephala performed better regarding biomass, dry matter and nodule production. Res. Agric., Livest. Fish.8(1): 25-31, April 2021